Microspatial Distributional Patterns of Vectors of Cutaneous Leishmaniasis in Pernambuco, Northeastern Brazil - Maria Rita Donalisio; A. Townsend Peterson; Pietra Lemos Costa; Fernando José da Silva; Hélio França Valença; Jeffrey J. Shaw; Sinval P. Brandão Filho (Journal of Tropical Medicine)
The purpose of this study is to analyze the spatial distribution and population trends through time of Lutzomyia species in a long-term focus of cutaneous leishmaniasis transmission in an Atlantic Forest area, northeastern Brazil. Sand fly populations of different ecological niches were monitored spatiotemporally in 2009. To summarize vegetation characteristics and phenology, we calculated the Normalized Difference Vegetation Index from Landsat images. Using niche modeling approaches, we assessed suites of environmental factors to identify areas of transmission risk. Although 12 species were detected, L. whitmani was the most abundant and broadly distributed across the area, particularly in peridomiciliary locations, and associated negatively with denser vegetation areas. On the other hand, L. complexa, L. sordelli, and L. tupynambai were found almost exclusively in forested areas (𝑃<0.05), and associated positively with denser vegetation. Lutzomyia species' occurrences are related to specific environmental combinations (with contrast among species) in the region.